Egg parasitoids of Edessa meditabunda (Fabricius) (Pentatomidae) in lettuce crop - Favetti, Bruna M. (2013)
Egg parasitoids of Edessa meditabunda (Fabricius) (Pentatomidae) in lettuce crop. This study evaluated the occurrence of parasitoids in eggs of the stink bug, Edessa meditabunda (Fabricius, 1794) (Heteroptera, Pentatomidae) found on lettuce crop in Mato Grosso State, Brazil. Samples were collected in the vegetable garden “Cheiro Verde”, in the municipality of Tangará da Serra, in curly lettuce. A bed of lettuce was selected randomly, where the eggs of E. meditabunda were collected. Five-hundred and seventy eight eggs of E. meditabunda were collected, 86.3% of them parasitized by Telenomus podisi Ashmead, 1893 (Hymenoptera, Platygastridae), Trissolcus urichi Crawford, 1913 (Hymenoptera, Platygastridae) and Neorileya albipes Girault, 1913 (Hymenoptera, Eurytomidae), representing respectively 57.0%, 38.2% and 4.8% of the emerged individuals. This is the first record of these three species parasitizing eggs of E. meditabunda in lettuce.